Erasmus on (Immoderate) Shame - Papadodēma, Ephē (Erasmus studies, 2026)
Erasmus did not set out a formal theory of shame, yet he developed a subtle and wide-ranging engagement with the emotion across his corpus, most prominently in the Adagia, his pedagogical texts, his letters, and his translation of Plutarch’s Περὶ δυσωπίας (De vitiosa verecundia). Situated within ancient and medieval debates on aidōs and pudor/verecundia, Erasmus adopts a conception of shame as a passion tied to fear of dishonor that may function as a quasi-virtue when regulated by conscience. Building on this inheritance, he participates in broader Renaissance discussions of emotion and character formation, most notably in the Adagia and his educational writings. In the former work, Erasmus catalogues and subtly reframes classical topoi on shame’s physiology, moral ambivalence, and relation to honor, fear, and necessity. In the educational writings, he recasts shame as a pedagogical instrument capable, ‘in its right measure’, of encouraging voluntary right action and cultivating decorum. Alongside this theoretical engagement, Erasmus also maps these distinctions onto his own self-understanding and self-presentation. His correspondence draws on the rhetoric of shame—largely understood as (over)bashfulness and persistent self-dissatisfaction—to fashion a persona of modesty and self-critique, with varied rhetorical and practical effects. More pointedly, Plutarch’s notion of δυσωπία, elaborated in his short essay Περὶ δυσωπίας and deliberately included in Erasmus’ Plutarch collection, furnishes Erasmus with both a technical vocabulary and a diagnostic lens for interpreting his own character and decisions. Read together, these texts shed light on Erasmus’ moral psychology of shame and on the role it plays in early modern humanist self-fashioning.